CORRELATIONS CHARACTERISTICS OF THE STRUCTURE-SENSITIVE PROPERTIES OF LIQUID METALS - V. N. Tsurkin; Ya. Yu. Dmitrishina (Литьë и металлургия, 2016)
The interconditionality of characteristics of major structure-sensitive properties of the liquid metals and the some parameters of electronic and atomic structure such as the first coordination number, electron charge and Boltzmann constant are displayed.